2017
DOI: 10.1128/jb.00842-16
|View full text |Cite
|
Sign up to set email alerts
|

CRISPR-Cas and Contact-Dependent Secretion Systems Present on Excisable Pathogenicity Islands with Conserved Recombination Modules

Abstract: Pathogenicity islands (PAIs) are mobile integrated genetic elements that contain a diverse range of virulence factors. PAIs integrate into the host chromosome at a tRNA locus that contains their specific bacterial attachment site, attB, via integrase-mediated site-specific recombination generating attL and attR sites. We identified conserved recombination modules (integrases and att sites) previously described in choleragenic Vibrio cholerae PAIs but with novel cargo genes. Clustered regularly interspaced shor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
11
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 60 publications
4
11
0
Order By: Relevance
“…The CRISPR-Cas region in 7 of 8 CRISPR-Cas positive non-O1 non-O139 strains sequenced in our study were found to be identical with that of strain HC-36A1 described previously 23 . However, comparisons of the entire sequence of the islands in our strains with those of previously described CRISPR-Cas containing genomic islands of strains S12, RC385, RC586 TM 11079-80, and HC-36A1 22 , 23 , showed that the islands found in 3 of our strains were > 95% identical to that found in strain HC-36A1 23 , whereas the islands in 4 of the strains were 70–74% identical to that in strain HC-36A1. The cas genes in one of our strains 173V1015 were found to share no sequence homology with that of the other islands analyzed, although the predicted protein sequence show more than 82% identity with Cas proteins of Salinivibrio costicola (Accession no.…”
Section: Resultssupporting
confidence: 82%
See 2 more Smart Citations
“…The CRISPR-Cas region in 7 of 8 CRISPR-Cas positive non-O1 non-O139 strains sequenced in our study were found to be identical with that of strain HC-36A1 described previously 23 . However, comparisons of the entire sequence of the islands in our strains with those of previously described CRISPR-Cas containing genomic islands of strains S12, RC385, RC586 TM 11079-80, and HC-36A1 22 , 23 , showed that the islands found in 3 of our strains were > 95% identical to that found in strain HC-36A1 23 , whereas the islands in 4 of the strains were 70–74% identical to that in strain HC-36A1. The cas genes in one of our strains 173V1015 were found to share no sequence homology with that of the other islands analyzed, although the predicted protein sequence show more than 82% identity with Cas proteins of Salinivibrio costicola (Accession no.…”
Section: Resultssupporting
confidence: 82%
“…cholerae non-O1 non-O139 strains were found to have the features of a genomic island (Fig. 6 ) as described previously 22 , 23 .
Figure 6 Schematic diagram showing the organization of the CRISPR-Cas loci carried by different cholera phages and V .
…”
Section: Resultssupporting
confidence: 67%
See 1 more Smart Citation
“…These included the T3SS-2α described in V. cholerae AM_19226 (refs. 50 , 51 ), the less-common T3SS-2β system described by Carpenter et al 51 , and a third putative T3SS system which most closely resembles genes present in the genomes of two virulent Chilean Vibrio anguillarum isolates 52 (Supplementary Fig. 10 ).…”
Section: Resultsmentioning
confidence: 78%
“…This is the case of Salmonella sp (ROD21 and SPI-7) [23], Escherichia coli UPEC (PAI I536, PAI II536, and PAI V536) [36], Klebsiella pneumoniae (GIE492) [37], Vibrio cholera (VPI-2 VSP-I and VSP-I) [38], and Pectobacterium atrosepticum (HAI2) [39]. These islands have significant structural conservation, displaying an unusual G + C profile, are inserted downstream a tRNA gene (usually Asp or Ser), have DRS at the 3´end of the PAI and typically encode paralogs of H-NS (hnsB) and/or an H-NS antagonist [26,40]. These data suggest that excisable PAIs are a conserved cluster of genes related to the family Enterobacteriaceae, and that excision might be an important event related with HGT and/or regulation of gene expression [24,35].…”
Section: Discussionmentioning
confidence: 99%